2010
DOI: 10.3354/meps08577
|View full text |Cite
|
Sign up to set email alerts
|

Developing visual deterrents to reduce sea turtle bycatch in gill net fisheries

Abstract: Visual cues play important roles in sea turtle foraging behavior and likely influence their interactions with fishing gear. Altering these cues may be a useful strategy to reduce the incidental catch of sea turtles in various fisheries. We examined the potential effectiveness of 3 visual cues -shark shapes placed along the length of the gill net, illumination of nets by LED lights, and nets illuminated with chemical lightsticks -in reducing bycatch of green sea turtles Chelonia mydas in gill nets. We then adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
129
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(136 citation statements)
references
References 31 publications
0
129
1
6
Order By: Relevance
“…To mitigate the bycatch problem in a short-time period, it is proposed the strategies used by Wang et al [35]: shark shapes placed along the length of the gill nets, illumination of nets by LED lights, and nets illuminated with chemical light sticks. Perhaps the use of deterrents similar to those described by Wang et al [35] may be tested by local fishermen (e.g., Kivuri fishermen were proactive in this study).…”
Section: Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…To mitigate the bycatch problem in a short-time period, it is proposed the strategies used by Wang et al [35]: shark shapes placed along the length of the gill nets, illumination of nets by LED lights, and nets illuminated with chemical light sticks. Perhaps the use of deterrents similar to those described by Wang et al [35] may be tested by local fishermen (e.g., Kivuri fishermen were proactive in this study).…”
Section: Conservationmentioning
confidence: 99%
“…Perhaps the use of deterrents similar to those described by Wang et al [35] may be tested by local fishermen (e.g., Kivuri fishermen were proactive in this study). It would be important to give incentive to local populations, for simple but important measures like searching and clearing the area of abandoned fishing gear.…”
Section: Conservationmentioning
confidence: 99%
“…Pengaruh penggunaan lampu LED hijau pada gillnet di penelitian ini, selanjutnya dibandingkan pada hasil beberapa penelitian yang telah dilakukan sebelumnya dalam upaya mengurangi bycatch penyu pada alat tangkap gillnet dengan menggunakan lampu hijau, disajikan pada Tabel 2. Lampu LED hijau yang digunakan pada penelitian ini sama dengan penelitian yang dilakukan oleh Wang et al (2010) dan Wahju et al 2014), sedangkan lampu LED hijau yang digunakan pada penelitian Ortiz et al (2014) berbeda. Meskipun demikian, pembandingan penelitian dirujuk berdasarkan penggunaan lampu yang menghasilkan cahaya berwarna hijau pada alat tangkap gillnet dan secara keseluruhan dapat mengurangi tangkapan penyu antara 40-85%.…”
Section: Analisis Pengaruh Penggunaan Lampu Led Hijau Terhadap Bycatcunclassified
“…Menurut Wang et al (2010); (2013); Gilman et al (2010); Ortiz et al (2016), penggunaan lampu atau cahaya pada alat tangkap merupakan upaya mitigasi untuk mengurangi bycatch penyu, dimana memberikan seperti sinyal peringatan untuk menghindari alat tangkap. Lampu LED hijau dipasang pada tali ris atas gillnet (bagian atas jaring gillnet), sedangkan profil cahayanya diketahui cenderung memancar ke arah horizontal yang membuat bagian atas jaring lebih terlihat, tetapi bagian tengah atau bawah jaring gillnet relatif tidak terlihat, sehingga penyu yang mengetahui keberadaan cahaya tersebut memberikan respons menghindar.…”
Section: Pembahasanunclassified
“…Our results indicate that Sechura Bay is an important foraging area and developmental habitat for green turtles and also possibly for critically endangered hawksbill turtles. This research found that a majority of sets having bycatch, given these catch rates; we recommend the identification and implementation of mitigation measures to reduce sea turtle bycatch, like illuminating nets with LED lights, shark silhouettes and use float lines without buoys (Gilman et al, 2010;Wang et al, 2010Wang et al, , 2013Ortiz et al 2016). To help maximize their uptake and effectiveness, such efforts to identify solutions should involve small-scale 611 Incidental capture of sea turtles in Sechura Bay, Peru 7 fishermen as well as scientists and other stakeholders and decision-makers.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%